An octahedral polyoxomolybdate–organic molecular cage. Issue 8 (7th January 2021) - Wang, Xin-Ying; Chen, Wei-Chao; Shao, Kui-Zhan; Wang, Xin-Long; Zhao, Liang; Su, Zhong-Min
Abstract : An unprecedented Mo–organic molecular cage built from interesting MoVI2O5 SBUs and BTC ligands, which has been successfully synthesized and systematically characterized, presents the first example of an isopolyoxomolybdate–organic molecular cage. Abstract : An unprecedented Mo–organic molecular cage built on interesting MoVI2O5 secondary building blocks and BTC ligands, which has been successfully synthesized and systematically characterized, presents the first example of an isopolyoxomolybdates(vi )–organic molecular cage. An investigation into the related Cs + -exchange experiment was performed in detail.